Identity Politics In The Campaign Tagline At The 2020 Sumenep Elections - Moh Zuhdi; Moh Ikmal (Fakultas Usluhuddin dan Dakwah IAIN Kediri, 2022)
This study wants to find out how the form of identity politics in the campaign tagline in the 2020 Sumenep Pilkada. This research is important to do, considering the messages in the campaign tagline as identity politics in the 2020 Sumenep Pilkada are interesting to study. This study uses a qualitative method. The object of this research is the text and narrative of political campaigns in the taglines